An investigation into the difficulties of integrating social services in South Africa - Valentine, Lucinda Jane (Department of Political Studies, 2022)
After the first democratic elections in 1994, the newly elected democratic government of South Africa tried to remedy social inequities from the past by implementing more development-oriented social policies. The Department of Social Development's Integrated Service Delivery Model (ISDM) is one of these efforts. However, the integration of social services has been fraught with challenges. During a practical placement at a community clinic in Fisantekraal in the Western Cape, the researcher, as a social work student, observed that many nongovernmental organisations (NGOs) were ignorant of additional social services available in the area. Amongst the social services being offered, the researcher discovered duplication, fragmentation, and gaps. As a result, a closer examination of these observations was required. Not even the government social development authorities knew about the ISDM. The social service providers in Fisantekraal did not know about the principles of the developmental approach and the Generic Norms and Standards for Social Welfare Services, stated in the ISDM. According to the ISDM, integrated service delivery requires collaboration between NGOs, government, and the private sector; consequently, research into promoting integration in social service delivery in South Africa is critical. The question that framed and led this study is what challenges confront efforts to promote integration in social services delivery in South Africa. In order to investigate these challenges, this study administered a sample survey to social service providers across government, non-profit organisations and private practitioners. According to the core findings, the great majority of social service providers understand the concept of integrated social services. However, the data revealed that translating a widespread understanding of the concept of integration faces many operational obstacles. Many service users do not have access to specialised services because of the cost and distance required to travel. In addition, inadequate communication hinders partnering with the government on a provincial and local level. The mindset of lowering workload by exploiting the incentive of collaborating vi with other organisations has yet to become commonplace, even though there has been some progress in this area in the past. Promoting collaboration proved to be one of the most significant barriers to integrating social services, along with budgetary and capacity constraints. The NGO sector is financially stretched, and many organisations believe that a lack of funding impedes them from integrating their services. However, the opposite should be the case because combining their services would allow them to share costs and workload. In addition, many organisations have their own objectives and directives, which militate against the establishment of unified goals. Collaboration with the government was the most major roadblock to reaching a goal consensus. This was owing to a lack of access to their social service practitioners and their rigid mandates. A significant number of respondents have also not received training on the ISDM, implying that they are unaware of the model's intricacies and thus unable to implement it. The study reveals that social services providers are ill-equipped to deliver integrated social services. There appears to be a lack of know-how about how to create strong and effective organisational collaborations on the ground. A thorough understanding of integrated social services is not taught in the South African social services field despite a strong appreciation for the value of the concept. A shift in mindset is necessary, and this may be possible if more widespread training on integrated social services is provided.